Setting of conditions for handling electric multiple units “Lastochka” - A. M. Brzezhovskiy; D. N. Arshintsev; I. V. Smelyanskiy; S. V. Tolmachev; D. E. Kiryushin (Вестник Научно-исследовательского института железнодорожного транспорта, 2016)
In 2013, JSC “Russian Railways” railway network was put into operation high-speed electric multiple unit (EMU) ES1 “Lastochka” of dual supply with asynchronous traction drive produced by Siemens on Desiro platform. In accordance with the requirements of safety standards, and later the Technical Regulations of the Customs Union TR CU 001/2011 “On safety of railway rolling stock” experimental EMUs ES1 and ES2G completed a full range of tests, including their final stage - the complex tests of dynamics and impact on railway tracks and turnouts. The article summarizes the results of comprehensive testing of new high-speed EMUs intended for commuter and regional passenger service. Methodology of the study is based on the works of professor M. F. Verigo and includes experimental determination of combination of indicators of dynamic qualities and impact of trains on railway tracks in the complex tests in a single point in time. Study results of the set of dynamic performance qualities and impact of EMUs ES1 and ES2G “Lastochka” on the railway track with help of experimental and experimental-design methods have allowed to give recommendations on the level of permissible speeds, including run through tangent track sections - 160 km/h; in curved sections with radius of more than 400 m permissible speed can be set in terms of non-exceedance of unbalanced lateral acceleration of 0.9 m/s2, in curves of radius less than 400 m - in terms of non-exceedance of unbalanced lateral acceleration of 0.7 m/s2. On the basis of this combination of indicators with Norms of calculation of the strength of railway tracks a table of permissible speeds for trains is defined, which, as a normative document of JSC “Russian Railways”, introduced in the areas of circulation of these trains.